Dietary Treatment Options for Depression among Diabetic Patient, Focusing on Macronutrients - Fahimeh Haghighatdoost; Leila Azadbakht (Journal of Diabetes Research)
There is a bidirectional adverse association between diabetes and depression. The odds for experiencing depressive symptoms in diabetic patients are two times more than nondiabetic persons, and depression is an independent predictor for the onset of diabetes. However, depression has been approximately unrecognized and untreated in two-thirds of diabetic patients, which may lead to worsened diabetes complications. A cornerstone strategy for managing depression among diabetic patients is the use of diet to improve both health problems. Because of similar pathophysiology for chronic diseases and depression, it seems that similar dietary recommendations could be useful. However, few studies have been conducted among diabetic patients. Regarding the complications of diabetes such as renal diseases and coronary heart diseases, the proper range of various macronutrients should be clarified in depressed diabetic patients as well as the proper type of each macronutrient. In this paper, we reviewed the available data on the treatment of depression in diabetic patients.